الوسطية الإسلامية في رواية يوما ما كنت إسلاميا للكاتب أحمد أبو خليل - Nur Hidayah (Center of Middle Eastern Studies (CMES): Jurnal Studi Timur Tengah, 2018)
Islamic moderation is the Islamic balance which includes all aspects of Islam, whether in the way of thinking and practical application. This word has another meaning, which are the best, ideal, proportion and moderation. But the emergence of Islamic movements such as Salafism, Muslim Brotherhood, or jama’ah Tabligh and Da'wah, which have acknowledged its centrality, has alienated Islam from its true moderation. Novel Yauman Ma Kuntu Islamiyyan by the Egyptian writer Ahmed Abu Khalil is a story about the main character, the generation who grew up in the environment of the Muslim Brotherhood and was influenced by the concept of these movements while searching for the true way of Islamic life. This study aims to understanding the concept of Islamic moderation of a main character by knowing the concept of Islamic moderation presented by the writer in this novel. This study will be conducted the social elements involved in this literary work to understand the social phenomena existing outside the literary text.